Perinatal Outcome in Term Pregnancy with Isolated Oligohydramnios: Retrospective Observational Study - Adhikari, Ayushma; Gurung, Tika Kumari; Adhikari, Shree Prasad (Journal of Nepalgunj Medical College, 2021)
Introduction: Isolated Oligohydramnios complicates 3 to 5% of pregnancy at term both in terms of fetal outcome and mode of delivery.Aims: To study the perinatal outcome in isolated oligohydramnios (Amniotic Fluid Index≤8) and compare the outcome between Borderline (Amniotic Fluid Index=5.1-8 cm) and Severe (